Analisis Profil Bobot Badan Tikus dan Gejala Toksis Pada Pemberian Ekstrak Etanol Daun Parang Romang (Boehmeria virgata) Terhadap Tikus Putih (Rattus novergicus): Analysis Profile of Body Weight and Toxic Symptom of Rats In The Administration of Ethanol Extract Parang Roman Leaves (Boehmeria virgata) To Male White Rats (Rattus novergicus - Magfirah, Magfirah; Christin, Vidya (Universitas Tadulako, 2020)
Traditional medicine is part of the Indonesian cultural heritage which has been used for generations and for centuries, but in general its safety has not been supported by adequate research. One of them is a parangromang which is empirically used by Makassar tribal healers as an antitumor. This study aims to determine theprofile Of body weight and toxic symptoms after 24 hours to 14 days including skinand fur changes, tremors and seizures, comaof rats in the administration of ethanol extract parang romang. White rats were divided randomly into 4 groups: group one was given 0.5% NaCMC, groups of two, three and four were given extract at a dose of 175 mg / KgBB, 550 mg / KgBB and 1750 mg / KgBB for 14 days, the bodyweights of rats on days 0, 7 and 14 days and toxic symptoms after 24 hours to 14 days.The results showed ethanol extract of parang romang leaves 550 mg / KgBB had an effect on increasing body weight of rats and there were no changes in skin and fur, spasms, tremor, coma and death. It can be concluded that the ethanol extract of parang romang leaves has a significant effect on increasing the weight profile of male white rats and there are no toxic symptoms.